Innovations in Affective Assessment in Arabic Language Books for Grade VII Based on Communicative Approach - Azmy, Muhammad Ulul; Baroroh, R Umi; Novian, Zailani; Salsabila, Sarah (Arabiyatuna: Jurnal Bahasa Arab, 2025)
Arabic language learning in Madrasah Tsanawiyah has implemented a communicative approach that emphasizes real language interaction. However, the Ministry of Religious Affairs' Arabic textbook for seventh grade does not provide assessment instruments that systematically assess the affective domain, so that students' progress in communication cannot be properly measured. This article aims to develop an affective assessment instrument that is integrated with the Ta'aruf material in the seventh grade Arabic textbook. This study uses a modified Borg & Gall Research and Development model, which includes the following stages: needs analysis, instrument design, expert validation, and product revision. The instruments developed are teacher observation sheets and student self-reflection sheets, which are compiled based on Krathwohl's affective taxonomy and a communicative approach. Expert validation was conducted by three validators consisting of two Arabic language education experts and one learning evaluation expert, with a Content Validity Index (CVI) result of 0.87, which is considered valid. This instrument is deemed suitable for use without requiring additional technical training for teachers, and is capable of helping to assess students' courage, self-confidence, cooperation, and respect in the communication process. Thus, this innovation has practical implications for teachers in applying authentic and sustainable affective assessment in the classroom, and can be developed in other chapters or further tested in field learning.